The reintegration of ex-combatants in the Angolan peace process - Chavez, Irma Sofia Chavez (My University, 2014)
Between 1994 and 1998 Angola underwent a major attempt to create peace. The programme for the reintegration of ex-combatants into civilian society was a component of this process. The purpose of this research report was to examine the nature of this programme comparatively in the international context and, in particular, to explore which of a few broad frameworks was used in the programme. These were identified as the Human Training (HT), Human Resources Management (HRM), and Human Development (HD) approaches. This examination also investigated the appropriateness of the framework. The social, political and economic context in which the programme took place were also explored, including the lessons learnt from the Angolan experience, which might have implications for similar processes elsewhere. The main finding of the research was that, in the case of Angola, the optimal approach would be one of Human Development, which is a broad approach encompassing the improvement of social, economic and political policies.
A research report submitted to the Faculty of Management, University of the Witwatersrand, in partial fullfilment of the requirements for the degree of Master of Management (in the field of public and development management ) February, 2000